Analisis Faktor Determinan dalam Upaya Pencegahan Stunting Anak Usia 2-5 Tahun - Ari Nofitasari; I Islaeli; Cici Yusnayanti (Universitas Aisyah Pringsewu, 2021)
Background Based on data from the Southeast Sulawesi Provincial Health Office, in 2019 there were 2920 stunted children, this figure is a combination of 1,811 short children and 1,109 very short children. In 2020, there were 1472 cases, with details of 983 short children and 489 very short children in Southeast Sulawesi. Based on these data, Southeast Sulawesi is a stunting emergency. Therefore, efforts to prevent stunting are needed. The aim of this study was to analyze the determinants of stunting prevention efforts in toddlers 2 - 5 years in Petoaha Village, Abeli District, Kendari City with a total sample of 103 toddlers. Methods The research method used an analytical cross-sectional approach. Sampling was taken by simple random sampling and analyzed by using the Chi-Square test. Results The research shows that there is a significant relationship between knowledge, education, socio-economic, early initiation of breastfeeding(IMD), exclusive breastfeeding and the prevention of stunting in Petoah Village, Abeli, Kendari City with the value of each variable (p = 0.000 less than 0.05). Conclusion there is a relationship between Knowledge, education, socioeconomic, IMD AND ASI exclusively with the prevention of stunting.Abstrak: Berdasarkan data Dinas Kesehatan Provinsi Sulawesi Tenggara pada tahun 2019terdapat sebanyak 2920 anak stunting, angka tersebut merupakan penggabungan dari 1.811 balita pendek dan 1.109 balita sangat pendek. Pada tahun 2020 mencapai 1472 kasus, dengan rincian sebanyak 983 balita pendek dan 489 balita sangat pendek di Sulawesi Tenggara. Berdasarkan datatersebut Sulawesi Tenggara termasuk keadaan darurat stunting, untuk itu diperlukan upaya pencegahan stunting. Tujuan dari penelitian ini adalah untuk menganalisis Determinan faktor upaya pencegahan stunting pada anak usia 2 – 5 tahun dikelurahan Petoaha Kecamatan Abeli Kota Kendari dengan jumlah sample 103 balita Metode penelitian menggunakan analitik dengan penedekatan cross sectional. Pengambilan sampel dengan simple random sampling dan dianalisis dengan uji Chi Square. Penelitian menunjukan bahwa terdapat hubungan signifikan antara pengetahuan, Pendidikan, Sosial ekonomi, IMD, ASI Esklusif dengan pencegahan stunting di Kelurahan Petoah, Abeli Kota Kendaridengan nilai masing-masing variable (p = 0.000 kurang dari 0.05) sehingga dapat disimpulkan bahwa terdapat hubungan antara Pengetahuan, pendidikan , sosial ekonomi, IMD DAN ASI esklusif dengan pencegahan stunting.